Excess Molar Volumes and Viscosities of Mixtures Containing Dimethylformamide (DMF) with benzene, o-xylene, 1, 4- Dioxane and Tetrahydrofuran at 298.15 K. - Kadhem, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Measurements of excess molar volumes VE , viscosities Î· , excess viscosities Î” ln Î·  and excess molar activation energies of viscous flow Î”GE , are reported for binary mixtures of dimethylformamide (DMF) with , benzene , o-xylene , 1,4- dioxane and tetrahydrofuran are reported from density and viscosity measurements at 298.15 k and at atmospheric pressure over the entire composition range . The excess values are positive for the mixture (DMF+ polar solvent) and negative deviation from ideality for the mixture (DMF + non-polar solvent) over the whole composition range and discussed in the light of molecular interaction in the mixture.